Recovery capacity, haemodynamic and blood lactate changes during training and competition in elite Congolese karate athletes - Moulongo, J. G. A.; Moussoki, J. M.; Massamba, E. L. S.; Massala Kitanga, F. N.; Tchissambou, B. P.; Mabiala Babela, J. R.; Massamba, A. (World Journal of Cardiovascular Diseases, 2020)
Rare are the studies which treated the effect of training and successive fights of karate on haemodynamic and blood lactate concentrations responses. Objectives: To evaluate and analyze the aerobic capacity of elite Congolese karate athletes, as well as their haemodynamic and blood lactate concentrations responses changes during Ruffier test and stimulated competition. Methods: Twelve karate athletes (6 seniors and 6 juniors) took part in the study. These karate athletes were selected within the national karate teams (senior and junior) of Congo-Brazzaville. Anthropometric, bioenergetic and haemodynamic (HR, SBP, DBP) parameters and blood lactate [La] concentrations were measured at rest, immediately after the end of Ruffier test and each fight (n = 3). Results: Peak aerobic power (PAP) and maximum oxygen uptake (VO2 max) values averaged 437 ± 23 watts and 57.61 ± 2.2 ml/kg/mn, values varying as function as age division (senior vs junior). The recovery index was 5.4 ± 3.4 for juniors and 6.8 ± 3.2 for seniors. SBP, HR and [La] concentrations increased significantly during fights, compared to the resting values. HRmax was 182.3 ± 1.6 bpm (89% theoretical HRmax) for seniors and 182.0 ± 13.5 bpm (86% theoretical HRmax) for juniors. Peak [La] concentrations were 10.3 ± 1.5 mmol/l for seniors and 10.8 ± 1.2 mmol/l for juniors. Conclusion: Congolese karate athletes call upon high levels of the anaerobic and aerobic capacities. The karate training program in Congo should emphasize more gold improvising lower body anaerobic power and endurance.